The Role of the Prosecutor's Office in Eradication of Corruption in Aceh Tamiang Regency - Fakhrur Razi; Riza Zarzani (International Journal of Society and Law, 2024)
Corruption is a serious violation of the social and economic rights of the community, becoming an extraordinary threat to the state. This study explores the role of the Prosecutor's Office in eradicating corruption in Aceh Tamiang Regency. The Prosecutor's Office has a strategic position as a law enforcer with special authority in handling corruption cases. This research aims to understand the role and obstacles faced by the Prosecutor's Office in these efforts. The methodology used includes juridical and empirical analysis. The findings show that collaboration between the Prosecutor's Office and related agencies is indispensable for the effectiveness of corruption eradication.